GENDER EQUITY: A STUDY OF WOMEN ENTREPRENEURS IN THE CARNAÚBA COMMUNITY - JATI/CE (Editora Impacto Científico, 2025)
Female entrepreneurship has been gaining prominence in the Carnaúba community, located in Jati, Ceará, Brazil. This descriptive, qualitative research examines women’s entrepreneurship as a means to promote gender equity. The study aims to characterize the profile of female entrepreneurs in Carnaúba, analyzing the challenges they face and the practices that strengthen their entrepreneurial endeavors. Data were collected through questionnaires and interviews. Results indicate that these entrepreneurs exhibit key traits such as proactivity, discipline, dedication, persistence, conflict management skills, and democratic leadership. The study also identifies major obstacles, including lack of initial financial support and the double burden of work and domestic responsibilities. Strengthening female entrepreneurship hinges on collective commitment—creating an environment that encourages, values, and supports women entrepreneurs while fostering equitable opportunities for business success. Additionally, the research highlights the advancement of gender equity in the local context.